Invention of a Summation Formula Accumulated With Hypergeometric Function (Global Journal of Science Frontier Research, 2012)
The main aim of this paper is to create a summation formula amassed with Hypergeometric function.
Keywords: Contiguous relation; Recurrence relation; Gauss second summation theorem